Pengaruh Pengungkapan Sustainability Report dan Penerapan Good Corporate Governance Terhadap Return Saham - Aulia, Desmalia; Sudrajat, Sudrajat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The phenomenon of environmental damage has now become a common problem. Most of the environmental damage that occurs is caused by industrial production activities. Greenpeace Indonesia revealed that the results of investigations related to coal mining activities in East Kalimantan Province have damaged the natural landscape and disrupted water and soil quality. Based on data released by the Mining Advocacy Network or JATAM, as much as 44% of the land in Indonesia has been granted for around 8,588 mining business permits. The concept of a sustainability report is currently one of the concepts that has emerged to help companies convey the responsibilities they have undertaken to commit to sustainable economic development. Apart from that, it is important for companies to implement good corporate governance because it can encourage the creation of markets that are efficient, transparent and consistent with statutory regulations. By disclosing sustainability reports and implementing good corporate governance as a form of company responsibility towards stakeholders and the environment, it is hoped that this will have a good impact on the company because it can increase stakeholder trust and will influence the company's stock return level. The sample selection in this study used a purposive sampling method. Sustainability reports are measured by analyzing the GRI G4 Guidelines report with 91 items. Good corporate governance in this research is proxied by independent commissioners, audit committees and foreign ownership. The results of this research show that economic aspects, social aspects, environmental aspects, independent commissioners, audit committees and foreign ownership have no effect on stock returns.